Childbearing and the changing nature of parenthood : the contexts, actors, and experiences of having children - Pisco Costa, Rosalina; Blair, Sampson Lee (Contemporary perspectives on family research ;, 2019)
Around the globe, the very conceptualization of family is associated with the relationship between a parent and a child. The birth of a child represents both the end of one experience, and the beginning of another. Entry into parenthood represents a fundamental shift in family structure and family dynamics, wherein the child brings new responsibilities within the family and upon the larger society, particularly in regards to population issues.In order to better understand the transitions into parenthood, this multidisciplinary volume of CPFR will address such topics as: employment and fertility, childbearing desires versus childbearing outcomes, the social media construction of parenthood, gender differences in childrearing, parental discipline and child outcomes, among others. This volume will contain research on parenthood and parenting from around the world, and is intended to provide a more global perspective of these issues. Given that these topics range across various disciplines, a variety of theoretical and methodological approaches are utilized in the research herein.